2023
DOI: 10.1155/2023/8183167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Nanoparticle Graphene Oxide on Flexural Strength of Glass Ionomer Cements

Abstract: Aim. Glass ionomer (GIC) is a widely used restorative material in dentistry, but it has relatively weak mechanical properties. In this research, the effect of graphene oxide (GO) on the flexural strength of GIC was investigated. Materials and Methods. In this experimental study, 60 GIC samples in 6 groups of 10 were prepared, including Group 1: control conventional glass ionomer (CGIC), Group 2: CGIC + 1% wt of GO, Group 3: CGIC + 2% wt of GO, Group 4: control resin-modified glass ionomer (RMGI), Group 5: RMGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The findings revealed that incorporating 2% by weight of GO into RMGIC led to an increase in its flexural strength. This finding holds significant clinical significance as it offers a means to enhance the mechanical properties of RMGIC, potentially improving its performance as a dental material [ 21 ]. Furthermore, the incorporation of 1% nGO into CGIC and RMGIC resulted in a notable decrease in gingival microleakage for CGIC and both occlusal and gingival microleakage for RMGIC.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that incorporating 2% by weight of GO into RMGIC led to an increase in its flexural strength. This finding holds significant clinical significance as it offers a means to enhance the mechanical properties of RMGIC, potentially improving its performance as a dental material [ 21 ]. Furthermore, the incorporation of 1% nGO into CGIC and RMGIC resulted in a notable decrease in gingival microleakage for CGIC and both occlusal and gingival microleakage for RMGIC.…”
Section: Introductionmentioning
confidence: 99%
“…FRC is a composite material made of polymer matrix, and is reinforced by fiber, which has tensile strength as well as high flexural strength 6 . The benefit of FRC is the minimum intervention, aesthetic compared to the metal dan can be done in one visit 7 . The addition of fiber as reinforcing material in composite resin has several benefits such as improving the strength and stiffness, durable against the fracture, able to lower the shrinkage 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforced composite is currently more widely used than porcelain fused to metal fixed prostheses, because of the increased demand for conservative and aesthetic restoration that is convenient because the restoration can adhere effectively to the teeth and cause minimal damage to the remaining teeth 1,2 . Fixed denture fiber reinforced composite is also chosen because it can be made directly in the clinic without going through laboratory procedures, and the nature of the material that does not corrode like metal material 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforced composite is a restoration consisting of a combination of fiber and resin matrix 1 . FRC in dentistry is widely applied to the base of removable denture made of acrylic resin, as a reinforcement of fixed dentures, periodontal splints, fixed orthodontic retainer and dental restoration 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation